17β-Estradiol Attenuates Neuropathic Pain Caused by Spared Nerve Injury by Upregulating CIC-3 in the Dorsal Root Ganglion of Ovariectomized Rats - Xu, Zhen-Zhen; Chen, Qin-Yi; Deng, Shi-Yu; Zhang, Meng; Tan, Chao-Yang; Yang Wang,; Ma, Ke-Tao; Li, Li; Si, Jun-Qiang; Zhu, Li-Cang (Frontiers in Neuroscience, 2019)
17β-estradiol plays a role in pain sensitivity, analgesic drug efficacy, and neuropathic pain prevalence, but the underlying mechanisms remain unclear. Here, we investigated whether voltage-gated chloride channel-3 (ClC-3) impacts the effects of 17β-estradiol (E2) on spared nerve injury (SNI)-induced neuropathic pain in ovariectomized (OVX) female Sprague Dawley rats that were divided into OVX, OVX + SNI, OVX + SNI + E2, OVX + SNI + E2 + DMSO (vehicle, dimethyl sulfoxide), or OVX + SNI + E2+Cltx (ClC-3-blocker chlorotoxin) groups. Changes in ClC-3 protein expression were monitored by western blot analysis. Behavioral testing used the paw withdrawal threshold to acetone irritation and paw withdrawal thermal latency (PWTL) to thermal stimulation. Immunofluorescence indicated the localization and protein expression levels of ClC-3. OVX + SNI + E2 rats were subcutaneously injected with 17β-estradiol once daily for 7 days; a sheathed tube was implanted, and chlorotoxin was injected for 4 days. Intrathecal Cltx to OVX and OVX + SNI rats was administered for 4 consecutive days (days 7–10 after SNI) to further determine the contribution of ClC-3 to neuropathic pain. Patch clamp technology in current clamp mode was used to measure the current threshold (rheobase) dorsal root ganglion (DRG) neurons and the minimal current that evoked action potentials (APs) as excitability parameters. The mean number of APs at double-strength rheobase verified neuronal excitability. There was no difference in behaviors and ClC-3 expression after OVX. Compared with OVX + SNI rats, OVX + SNI + E2 rats showed a lower paw withdrawal threshold to the acetone stimulus, but the PWTL was not significantly different, indicating increased sensitivity to cold but not to thermal pain. Co-immunofluorescent data revealed that ClC-3 was mainly distributed in A- and C-type nociceptive neurons, especially in medium/small-sized neurons. 17β-estradiol administration was associated with increased expression of ClC-3. 17β-estradiol-induced increase in ClC-3 expression was blocked by co-administration of Cltx. Cltx causes hyperalgesia and decreased expression of ClC-3 in OVX rats. Patch clamp results suggested that 17β-estradiol attenuated the excitability of neurons induced by SNI by up-regulating the expression of ClC-3 in the DRG of OVX rats. 17β-estradiol administration significantly improved cold allodynia thresholds in OVX rats with SNI. The mechanism for this decreased sensitivity may be related to the upregulation of ClC-3 expression in the DRG.